Предмет: Алгебра,
автор: Kassmariks
Раскройте скобки
а)(x+3)²
б)(2-y)²
Используя формулу (а+b)(a-b)=a²-b², выполните
a)28·32
б)67·73
Решите уравниение:3(x+1)(x-1)=2(x-2)(x+2)x²+2x
Ответы
Автор ответа:
0
а)(x+3)²=x²+6x+9
б)(2-y)²=4-4y+y²
a)28·32 =(30-2)(30+2)=30²-2²=900-4=896
б)67·73=(70-3)(70+3)=70²-3²=4900-9=4891
3(x+1)(x-1)=2(x-2)(x+2)+x²+2x
3(x²-1)=2(x²-4)+x²+2x
3x²-3=2x²-8+x²+2x
2x=5
x=2,5
б)(2-y)²=4-4y+y²
a)28·32 =(30-2)(30+2)=30²-2²=900-4=896
б)67·73=(70-3)(70+3)=70²-3²=4900-9=4891
3(x+1)(x-1)=2(x-2)(x+2)+x²+2x
3(x²-1)=2(x²-4)+x²+2x
3x²-3=2x²-8+x²+2x
2x=5
x=2,5
Похожие вопросы
Предмет: Қазақ тiлi,
автор: bibinur2085
Предмет: Английский язык,
автор: Аноним
Предмет: Алгебра,
автор: 6578946
Предмет: Химия,
автор: Okschud